ADMINISTRATIVE AND LEGAL REGIME OF THE NORTHERN DELIVERY AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF THE NORTH AND THE ARCTIC ZONE OF RUSSIAN FEDERATION - Galina V. Goncharuk (Russian Studies in Law and Politics)
The relevance of the issue studied in the article lies in the fact that ensuring the sustainable development of the North and the Arctic zone of the Russian Federation (hereinafter also referred to as the Russian Arctic) is a priority direction of modern state policy. One of the factors ensuring the stability and sustainability of the development of the North and the Russian Arctic is northern deliveries. The purpose of the study is to analyze the legal regulation of northern imports, characterize its role in order to ensure the sustainable development of the North and the Russian Arctic. To conduct the research, the comparative legal method, the formal legal method, the historical method, analysis, synthesis, and logical methods were used. The article examines the legal and organizational foundations for the sustainable development of the North and the Russian Arctic, highlights its relationship with food security, and notes the positive experience of Canada in the process of legal regulation of the target state of the Arctic part of the country - sustainable development. The sustainable development of the North and the Russian Arctic is considered in the article mainly within the framework of its socio-economic aspect. As a result of the study, conclusions were drawn that the development of legal regulation of northern imports is one of the factors in the sustainable development of the North and Arctic of Russian Federation.